2015
DOI: 10.1002/cctc.201500337
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nitrogen‐Doped Carbon from Polyacrylonitrile and its Application as a Solid‐Base Catalyst

Abstract: N-doped carbon (N-carbon) materials were prepared from a commercial polyacrylonitrile (PAN) by calcination and subsequent ammoxidation and these were used for a model reaction of Knoevenagel condensation of benzaldehyde and ethyl cyanoacetate. The catalytic activity of the calcined PAN for the reaction was very low, but it was greatly enhanced by the ammoxidation and the enhancement depended on both the calcination and ammoxidation temperatures. X-ray photoelectron spectra indicated the presence of pyridine-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The present authors prepared nitrogen-doped carbon materials by a simple method in which an activated carbon (AC) was treated by a mixture of ammonia and air at temperatures of 400 -800ºC. Those nitrogen-doped AC materials were shown to catalyze different types of organic reactions including Knoevenagel condensation [8,9], transesterification [8], reduction [10], and oxidation [11,12]. One of interesting results obtained is chemoselectivity in the reduction of aromatic substrates by hydrazine [10].…”
Section: Introductionmentioning
confidence: 99%
“…The present authors prepared nitrogen-doped carbon materials by a simple method in which an activated carbon (AC) was treated by a mixture of ammonia and air at temperatures of 400 -800ºC. Those nitrogen-doped AC materials were shown to catalyze different types of organic reactions including Knoevenagel condensation [8,9], transesterification [8], reduction [10], and oxidation [11,12]. One of interesting results obtained is chemoselectivity in the reduction of aromatic substrates by hydrazine [10].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the carbocation attacks the carbon atom of the carbonyl group of benzaldehyde, producing ECC through the dehydration of an alcohol intermediate compound. It was also reported that, for the Knoevenagel reaction, the catalytic performances of the most active N-AC and N-PAN were comparable with, or higher than those of some solid base catalysts reported so far [25]. Thus, N-AC and N-PAN could be alternatives to conventional solid base catalysts.…”
Section: Use Of Nitrogen-doped Activated Carbon For Base Catalyzed Rementioning
confidence: 71%
“…However, similar to the case of Knoevenagel reaction, liquid pyridine molecules had no activity for the oxidation reaction. The significance of the presence of pyridine-type nitrogen atoms It was also reported that, for the Knoevenagel reaction, the catalytic performances of the most active N-AC and N-PAN were comparable with, or higher than those of some solid base catalysts reported so far [25]. Thus, N-AC and N-PAN could be alternatives to conventional solid base catalysts.…”
Section: Use Of Nitrogen-doped Activated Carbon For Aerobic Oxidationmentioning
confidence: 91%
See 2 more Smart Citations